Legal Protection for Suspect on Sexual Harassment Against Children With Disabilities at The Examination Stage - Putu Edy Sukaryawan; Simon Nahak; I Ketut Widia (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2018)
Abstract Sexual malpractice against children with disabilities in recent years is an increasing trend in quality and quantity throughout Indonesia. In that case, there is a growing issue in the community. It is that legal protection for suspects of the cases of sexual harassment against children with disabilities at the stage of examination is not optimal. This study seeks to address the issue in question by revealing the procedures of providing legal aid to perpetrators of sexual harassment against children with disabilities at the examination stage and to the impacts of such legal protection. The type of research used in the study is empirical law research. The results of data analysis indicate that: 1) procedures of providing legal aid in the form of protection to perpetrators of sexual harassment against children with disabilities are adjusted according to the provisions contained in the Criminal Procedure Code; 2) the impact of legal protection toward such perpetrators against sexual harassment is that the number of crimes decreases. Keywords: Children With Disabilities; Legal Protection; Sexual Harrasment.